Non-metastatic ileal leiomyosarcoma in an aged pouter pigeon (Columba livia) - GORNATTI CHURRIA, CD; LOUKOPOULOS, P (Journal of the Hellenic Veterinary Medical Society, 2018)
Intestinal smooth muscle neoplasms are rarely reported in avian species. An aged male pouter pigeon (Columba livia) had anorexia, somnolence, progressive emaciation and yellowish diarrhea of four days’ duration and died despite antibiotic and antiparasitic treatment. At necropsy, the ileum bore a whitish, nodular, 0.8 cm in diameter mass severely narrowing the lumen. Histopathologically, the ileal mass was a well-demarcated, expansile neoplasm severely expanding the tunica muscularis and invading the mucosa. The neoplasm was composed of densely packed spindle cells with elongated nuclei arranged in broad interlacing bundles, and showing mild anisocytosis and anisokaryosis. Immunohistochemically, the neoplasm was positive for desmin and smooth muscle actin, and negative for cytokeratin, and c-kit. The gross, histopathologic and immunohistochemical findings provided the diagnosis of ileal leiomyosarcoma. This is the first report of an ileal leiomyosarcoma in Columbiformes and one of few intestinal smooth muscle neoplasms described in birds.